Natural polysaccharides as promising biologics from traditional medicine: Next-generation therapeutic strategies for breast diseases - Song Wei; Yi Li; Xiujuan Li; Fulei Liu; Jingwei Xue (Food Science and Human Wellness, 2026)
Abstract Breast diseases (such as mastitis, mammary hyperplasia, and breast cancer) pose serious threats to women's health, necessitating the development of safe and effective treatment strategies. Natural polysaccharides have attracted considerable attention due to their unique biocompatibility, low toxicity, and multifaceted bioactivities, including antimicrobial, anti-inflammatory, immunomodulatory, and antitumor effects. This review systematically examines the therapeutic potential and mechanisms of natural polysaccharides and their derivatives in breast diseases. For mastitis, polysaccharides alleviate symptoms by modulating gut microbiota, exerting direct antibacterial effects, and providing antioxidative and anti-inflammatory protection. Polysaccharide-based nanomaterials further enhance diagnostic sensitivity, drug-targeting efficiency, and antibacterial performance. In mammary hyperplasia, polysaccharides intervene by regulating gut microbiota homeostasis, inhibiting abnormal cell proliferation, and exerting antioxidative and antifibrotic effects. In breast cancer treatment, polysaccharides not only directly suppress tumor cell proliferation, migration, apoptosis, and autophagy but also enhance antitumor immunity through immunomodulation. Moreover, polysaccharide-based biomaterials as drug carriers significantly improve the targeting ability and synergistic therapeutic efficacy of chemotherapeutic agents. Although natural polysaccharides demonstrate promising potential in breast disease management, their precise mechanisms of action, structural optimization, and clinical translation require further investigation. Future research integrating nanotechnology and multidisciplinary approaches may establish polysaccharides as a groundbreaking strategy for precision therapy in breast diseases.